2012
DOI: 10.1111/j.1523-5378.2012.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Greater Than 95% Success with 14‐day Bismuth Quadruple Anti‐Helicobacter pylori Therapy: A Pilot Study in US Hispanics

Abstract: This pilot study supports the concept that 14-day OBMT therapy is likely to be more efficacious for H. pylori eradication (Grade A, PP basis) than a 10-day course where metronidazole resistance is suspected. If confirmed, 14 days should be recommended in populations where metronidazole resistance is common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…The most common for early stopping was the presence of an adverse event. As would be expected, treatment success increased as the duration of therapy increased (Table 1, Figure 5) 43 . The cure rate ITT was 70% and PP was >95%.…”
Section: Adherence (Compliance) With Bismuth Quadruple Therapysupporting
confidence: 66%
See 1 more Smart Citation
“…The most common for early stopping was the presence of an adverse event. As would be expected, treatment success increased as the duration of therapy increased (Table 1, Figure 5) 43 . The cure rate ITT was 70% and PP was >95%.…”
Section: Adherence (Compliance) With Bismuth Quadruple Therapysupporting
confidence: 66%
“…An example is a 14 day treatment trial using a formulation in which the antibiotics and bismuth are contained within the same capsules (i.e., Pylera) and omeprazole 20 mg b.i.d. 43 . Forty-seven subjects were entered and 12 (25.5%) failed to take the planned 14 days of therapy.…”
Section: Adherence (Compliance) With Bismuth Quadruple Therapymentioning
confidence: 99%
“…Possibly, the most effective BQT is the one employing the highest practical doses of the single drugs for the longest reasonable duration, such as 14 days. A one-arm, open-label pilot study of 47 H. pylori -infected, asymptomatic/mildly dyspeptic adult Hispanic residents of El Paso, Texas showed a per-protocol effectiveness of 97.7% for BQT given for 14 days [34]. In this study the combination capsule of bismuth, metronidazole, and tetracycline (daily doses: 1,680, 1,500, and 1,500 mg, respectively) plus omeprazole (daily dose: 40 mg) was used.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ITT eradication rate with modified bismuth quadruple therapy was 92.7% in a recent randomized study in Chinese patients [79] . A pilot study in United States Hispanics showed that 14-d bismuth quadruple anti-H. pylori therapy achieved a > 95% eradication rate [80] . However, in some studies the eradication rate of bismuth quadruple therapy was < 80% [81][82][83] .…”
Section: Publication Treatment Duration Patients Therapy Regimen Eradmentioning
confidence: 99%